PENGARUH FAKTOR-FAKTOR KINERJA INDIVIDUAL KARYAWAN TERHADAP EFEKTIVITAS PENGGUNAAN SISTEM INFORMASI AKUNTANSI - Vipraprastha, Tiksnayana; Sari, Maria M.Ratna (E-Jurnal Akuntansi; Vol 15 No 3 (2016), 2016)
Factors that affect the individual employee's performance is closely related to work experience, training, education, and incentives. The aim of this study was to determine the effect of work experience, training, education and incentives on the effectiveness of the use of accounting information systems. The population in this study were all employees of the branch office of PT. Bank Negara Indonesia (Persero) Tbk. in Badung, Bali Province. The samples used were 51 respondents with purposive sampling method. Methods of data collection using (1) interview (2) questionnaire. The analysis technique used is multiple linear regression analysis. Based on the analysis and hypothesis testing can be concluded that the variables (1) work experience positive effect on the effectiveness of the use of accounting information systems, (2) training has positive influence on the effectiveness of the use of accounting information systems, (3) the level of education has positive influence on the effectiveness of the use of information systems accounting, (4) incentive positive influence on the effectiveness of the use of accounting information systems.
Keywords: Effectiveness Using Accounting Information Systems, Work Experience, Training, Education Level, Incentives